MODELO DE ORGANIZAÇÃO EM REDE EM ECOSSISTEMAS DE INOVAÇÃO: Relato Técnico a partir do caso do Vale do Genoma - LORENZO JUNIOR, PAULINO FRANCISCO (2023)
This academic research presents a case study on the network-based organization model in innovation ecosystems, based on the case of the Vale do Genoma. The research addresses problems and challenges faced by institutions/organizations in this complex and collaborative environment, proposing solutions and applying academic knowledge in a practical and direct way. The research uses a qualitative approach, involving the collection of data on people, places, and processes through the researcher’s direct contact with the object being studied. Methods such as semi-structured interviews, participant observation, and document analysis were used. As a result, it presents valuable information on how to operate in innovation ecosystems and how academic institutions, investors and entrepreneurs can contribute to the development of these ecosystems.In addition, the research presents an innovative intervention proposed by the researcher, which consists of the introduction of a proprietary methodology to improve governance and promote the sustainable development of the innovation ecosystem in the Genome Valley. The research also allowed the obtaining of valuable insights to improve governance and promote the sustainable development of the innovation ecosystem in the Genome Valley.